Exporting - Paliwoda, Stan (Henry Stewart Talks, 2009)
What exporting delivers, Foreign market research problems, Public policy dimension, Political intervention in business, Market entry, Internationalization benefits, Where to go and how to do it?, Envisioning opportunity, Determinants of export performance, Four different meanings of 'yes', Present and future challenges